Psychology in contemporary China - Brown, L. B. (Laurence Binet), 1927-2011 (Pergamon Press, 1981)
Psychology in Contemporary China focuses on the advancement of psychology in China and the different areas to which this field is applied. The book proceeds by outlining the evolution, nature, and characteristics of Chinese psychology. The text then points out that studies on this discipline is generally difficult, because of the lack of publication of resources in English. The process of learning this field is often done through visitations, with specialists going to China to conduct research and lectures. The text investigates the evolution of psychology in China, as well as its progress thr.